2011
DOI: 10.1667/rr2377.1
|View full text |Cite
|
Sign up to set email alerts
|

Radon, Smoking and Lung Cancer Risk: Results of a Joint Analysis of Three European Case-Control Studies Among Uranium Miners

Abstract: A combined analysis of three case-control studies nested in three European uranium miner cohorts was performed to study the joint effects of radon exposure and smoking on lung cancer death risk. Occupational history and exposure data were available from the cohorts. Smoking information was reconstructed using self-administered questionnaires and occupational medical archives. Linear excess relative risk models adjusted for smoking were used to estimate the lung cancer risk associated with radon exposure. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 63 publications
4
88
0
6
Order By: Relevance
“…Working level month is defined as the cumulative exposure from breathing an atmosphere at a concentration of 1 working level for a working month of 170 h. mortality at exposure levels as low as 50 WLM. This analysis was confirmed by a recent analysis including information from the large German Wismuth cohort (Leuraud et al, 2011). This is based on a common reach program, conceived on European level, and including information about tobacco consumption as well as annual radon decay exposure.…”
Section: Dose-response Relationship Based On Large Joint Analysesmentioning
confidence: 52%
“…Working level month is defined as the cumulative exposure from breathing an atmosphere at a concentration of 1 working level for a working month of 170 h. mortality at exposure levels as low as 50 WLM. This analysis was confirmed by a recent analysis including information from the large German Wismuth cohort (Leuraud et al, 2011). This is based on a common reach program, conceived on European level, and including information about tobacco consumption as well as annual radon decay exposure.…”
Section: Dose-response Relationship Based On Large Joint Analysesmentioning
confidence: 52%
“…Or where the populations are separate, for example ATS and SHS, they can be added. In a few situations in which synergistic interactions have been documented, for example smoking and radon, the impact of the two together is greater than the sum of the two independently (15). The level of interaction among air pollution exposure categories is not well understood, which is why no aggregate total was shown in the CRA-2010 for air pollution.…”
Section: Resultsmentioning
confidence: 99%
“…In 1999, the BEIR VI report presented results based on six miner studies having partial smoking information, which supported a sub-multiplicative interaction between smoking and radon on lung cancer [54]. A similar but non-significant submultiplicative interaction was observed in a recent collaborative analysis of three case-control studies in Europe in which smoking information was constructed based on selfadministered questionnaires and occupational medical archives [60]. The ERR/WLM was 0.010 (95 % CI 0.002, 0.078) for never smokers and 0.005 (95 % CI 0.002, 0.13) for ever smokers (P interaction=0.42).…”
Section: Occupational Exposuresmentioning
confidence: 75%
“…Studies of uranium miners have additionally provided important evidence regarding age-and time-related modifiers, including a decline in risk with increasing time since exposure and, to a lesser extent, attained age. Several miner studies have shown an inverse modifying effect of exposure rate, but this effect was not observed at lower levels of cumulative exposure [54,59,60]. Cigarette smoking is another potentially important effect modifier; however, smoking data have generally been limited in uranium miner studies.…”
Section: Occupational Exposuresmentioning
confidence: 99%